Properties of concrete containing crushed palm oil clinker as partial fine aggregate replacement - M. A., Sulaiman; Mohamad Idris, Ali; M. Y., Al-Amri; Khairunisa, Muthusamy; A. M., Albshir Budiea; N., Nordin; Youventharan, Duraisamy; R., Othman (2019)
The growing demand for sand supply for construction industry use especially in concrete production drives the sand mining industry to flourish. However, excessive sand mining would affect the river environment, aquatic life and water quality. At the same time, the increasing quantity of palm oil clinker, which is a by-product at palm oil mill disposed at landfill, poses negative impact to the environment. The use of palm oil clinker waste as sand replacement in concrete production would be able to reduce the use of natural sand from the river and dumping of clinker waste at landfill. The current research investigates the fresh and mechanical properties of concrete containing palm oil clinker as partial fine aggregate replacement. A total five concrete mixes were produced. The control specimen was prepared by using 100% natural sand. Other mixes were formed by integrating crushed palm oil clinker as partial fine aggregate replacement ranging from 10%, 20%, 30% and 40%. All specimens were water cured up to 28 days. The specimens were subjected to slump test, compressive strength test, flexural strength test and water absorption test. The finding shows that suitable amount of palm oil clinker can be used as partial fine aggregate replacement in concrete production. Concrete containing palm oil clinker up to 40% replacement exhibits water absorption value lower than 10%, thus classified as good quality concrete.